Aromatherapy Lavender to Decrease Dysmenorrhea in Teenage Girls - Dwi Ertiana; Agustina Nur Pratami (poltekkes kemenkes mataram, 2021)
Dysmenorrhea can bother daily activity so it requires treatment to reduce it. By using aromatherapy lavender, is one of ways to overcome. This research intends to investigate the effect of giving aromatherapy lavender towards the reduction dysmenorrhea scale of teenage girls.This research uses quasy experiment. The independent variable is aromatherapy lavender & the dependent variable is dysmenorrhea pain. This research was conducted in Samiran village, subdistrict of Selo, Boyolali on 28th July–15th August 2020. Populations was 23 respondents. Sampling technique used purposive sampling with 22 respondents. Instruments used was questionnaire, aromatherapy lavender and SOP. Data analysis used was wilcoxon signed rank test. The result of the influence of giving aromatherapy lavender in the control group was moderate pain as much as 31.8% and the mild pain treatment group was 27.3%. Statistical test analysis by using wilcoxon signed rank test got the value 0,003 ≤ α 0,05. It showed the effect of giving aromatherapy lavender against reduction of dysmenorrhea scale. The aromatherapy lavender was proven to be able to reduce dysmenorrhea scale towards teenage girls. It was caused by aromatherapy lavender contains linalool dan linalyl asetat which was able to relax the nerve system and strained muscles.